Teaching Vocabulary By Using Hypnoteaching To Second Semester Students Of Bandar Lampung University - Fransiska Anggun Arumsari (Bandar Lampung University, 2015)
Success of a teaching learning process is influenced by a method of learning that is used in a class. A method can support the teaching learning process. Therefore a teacher must choose an appropriate method. There is a new method that is recently talked in Indonesian educational world. It is called hypnoteaching. “Hypnoteaching forms of a learning method which is creative, unique and also imaginative”[1]. The purpose of this research is to observe whether the hypnoteaching influences students in learning English vocabulary. Moreover a researcher also wants to know how this method influences students in vocabulary teaching learning process. The research is a qualitative research that uses 15 second semester students as samples. It is held in Bandar Lampung University.The research uses interview, observation and test in collecting data. The research finds thathypnoteaching influences the teaching learning process. Hypnoteaching can create happy, relaxed and enthusiastic condition in vocabulary class so it can improve student’s vocabulary mastery.